2008
DOI: 10.1016/j.jmb.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

ArPIKfyve Homomeric and Heteromeric Interactions Scaffold PIKfyve and Sac3 in a Complex to Promote PIKfyve Activity and Functionality

Abstract: PtdIns(3,5)P 2 is vital in differentiation and development of multicellular organisms because the knockout of the PtdIns(3,5)P 2 -synthesizing enzyme PIKfyve or its associated regulator, ArPIKfyve, is lethal. In previous work with endogenous proteins we identified that Sac3, a phosphatase that turns over PtdIns(3,5)P 2 , associates with the PIKfyve-ArPIKfyve biosynthetic complex. However, whether the three proteins suffice for the organization/maintenance of this complex (referred to as PAS complex), how they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
121
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(139 citation statements)
references
References 41 publications
18
121
0
Order By: Relevance
“…In line with the requirement for PtdIns(3,5)P 2 in maintaining proper balance between membrane removal (fission) and membrane insertion (fusion), disrupted function of PIKfyve, the sole enzyme for PtdIns(3,5)P 2 synthesis, is phenotypically manifested by endosome vesicle swelling and endomembrane vacuolation seen in a number of mammalian cell types (7). As unraveled recently, PIKfyve is engaged in an unusual physical interaction with the phosphatase Sac3 that turns over PtdIns(3,5)P 2 , forming a common endogenous complex (the PAS core complex) organized by the PIKfyve activator ArPIKfyve (9,14). The ternary association, scaffolded by ArPIKfyve homomeric interactions, activates the PIKfyve kinase as evidenced by recent data for reduced PIKfyve activity upon disintegration of the PAS core (14).…”
mentioning
confidence: 84%
“…In line with the requirement for PtdIns(3,5)P 2 in maintaining proper balance between membrane removal (fission) and membrane insertion (fusion), disrupted function of PIKfyve, the sole enzyme for PtdIns(3,5)P 2 synthesis, is phenotypically manifested by endosome vesicle swelling and endomembrane vacuolation seen in a number of mammalian cell types (7). As unraveled recently, PIKfyve is engaged in an unusual physical interaction with the phosphatase Sac3 that turns over PtdIns(3,5)P 2 , forming a common endogenous complex (the PAS core complex) organized by the PIKfyve activator ArPIKfyve (9,14). The ternary association, scaffolded by ArPIKfyve homomeric interactions, activates the PIKfyve kinase as evidenced by recent data for reduced PIKfyve activity upon disintegration of the PAS core (14).…”
mentioning
confidence: 84%
“…WT/KO -We have recently revealed that PIKfyve associates with the ArPIKfyve scaffold and Sac3 phosphatase in a regulatory ternary assembly, called the PAS complex, that relays two opposing enzymatic activities, synthesis and breakdown of PtdIns(3,5)P 2 (17,18). Considering a potential regulatory mechanism at the level of the Sac3 phosphatase as a means to counterbalance the loss of PtdIns(3,5)P 2 (and probably PtdIns5P) in the PIKfyve WT/KO genotype, we next examined the total protein levels of Sac3 and ArPIKfyve as well as their relative amounts engaged in the association with PIKfyve.…”
Section: Reduced Formation Of Pikfyve-arpikfyve-sac3 (Pas) Regulatorymentioning
confidence: 99%
“…the PtdIns(3,5)P 2 -specific phosphatase Sac3, which turns over PtdIns(3,5)P 2 to PtdIns3P (13,14). This interaction is indirect and is promoted by ArPIKfyve, an adapter protein that associates with and stabilizes Sac3 in a heterooligomeric complex (15)(16)(17). PIKfyve binds efficiently only to the ArPIKfyve-Sac3 complex to form a triple heterooligomer in which Sac3 fulfills a dual function (17,18).…”
mentioning
confidence: 99%
See 2 more Smart Citations